Evaluation of University Library Buildings in France, the Second Survey (2000–2007) - Bisbrouck, Marie-Françoise (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
After having described the historic perspective in which French university buildings and academic libraries were constructed or reconstructed since the middle of the 1950s, the author describes the survey she conducted in 2007 among colleagues who had opened 22 new or restructured library buildings. She presents the first results of the survey and compares them with the results of the earlier survey (1999–2000) she conducted, which concerned 30 library buildings. She tries to determine which changes have taken place in the past eight to ten years and focuses on the continuous training effort geared to improve head librarians’ knowledge in the field of library buildings. And this training effort works!